FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS HALMAHERA KOTA SEMARANG - Annisa Yasamina Zahra (2023)
Introduction: Toddler period is a very influential time in a child's growth. Fulfillment of nutritional needs in a timely manner has an influence on nutritional status in order to be able to develop and carry out functions optimally. The cause of undernourished toddlers has many factors where the number one cause in Indonesia according to WHO is diarrheal disease with a prevalence of 80% mortality, diarrhea can be caused by low knowledge about feeding and low economic conditions can cause children not to get enough nutrition. This study was conducted to determine the factors that influence the nutritional status of children under five. Methods: This study is an observational analytic with a cross sectional approach. The total sample was 109 people, with a sampling technique of proportionate stratified random sampling in 29 posyandu. Chi-Square analysis was used to test the data. Results: The results showed that the majority of respondents with a high level of education (80.7%), housewives (56%), had a low level of income (56.9%), had a large number of family members (57.8%), and had a sufficient level of knowledge about toddler nutrition (67%). Chi-Square test results show that the mother's education variable p value=0.701 (p>0.05), occupation p value=0.971 (p>0.05), income p value=0.589 (p>0.05), the number of family members p value=0.593 (p>0.05), knowledge has a value of p=0.009 (p<0.05) Conclusion: Knowledge is associated with the nutritional status of toddlers. The variables of education, occupation, income, and number of family members are not related to the nutritional status of children under five. This can occur because of the advanced and sophisticated technology that causes respondents with various educational backgrounds, various jobs, different opinions and the number of members can access information about toddler nutrition.